Multimodal approach in the development of the English reading skill. - Cabrera Nacevilla, Michelle Andrea (2023)
This bibliographic and documentary study concentrates on the multimodal approach to developing English reading skills. The study widely explores the multimodal approach, focusing on communication processes, learning styles, didactic resources, and learning environments. Additionally, it analyzes aspects involved in reading competency development, such as linguistic competencies, reading dimensions, models, and strategies. This study was conducted by extensively collecting and analyzing several scientific articles, reports, and books related to the subject, adhering to the guidelines of a qualitative research approach with a descriptive level. Besides, the university repository database and academic search engines, which include Google Scholar, Scopus, Eric, ProQuest, ResearchGate, and Redalyc, were fundamental. Furthermore, manual filters fulfilled the guidelines established by the institution to select the information and keywords of the study variables. The findings demonstrate that the Multimodal Approach application, when correctly implemented, is relevant in enhancing students' reading skills.